Transients in the errorbox of GW190814 - de Wet, Simon (Department of Astronomy, 2021)
We are now firmly in the era of multi-messenger astronomy. The detection of the first binary black hole (BBH) merger in GW150914 [1] opened up the era of gravitational wave astronomy, with a further 9 such mergers being detected during the first two observing runs (O1 and O2) of the LIGO Scientific and Virgo Collaborations (LVC). The first – and currently only – multi-messenger source was detected during O2 and was caused by the merger of two neutron stars in a binary system (BNS) [2]. The electromagnetic (EM) counterparts to GW170817 [3] were observed across the EM spectrum by numerous observing facilities, with implications across a vast range of scientific disciplines. Optical/nearinfrared observations demonstrated that the emission was due to a kilonova powered by the radioactive decay of r-process material produced during the merger. For the first time short gamma-ray bursts were convincingly linked to BNS mergers, as observed in GRB170817A [3]. The third LVC observing run (O3) began 2019 April 1 and concluded 2020 March 27. The signal from GW190425 [4] was likely caused by the coalescence of two neutron stars, with the system having a larger total mass than any currently known BNS system. Furthermore, the detection of GW190412 revealed the first BBH merger with a clearly unequal mass ratio of q = m2/m1 = 0.28 along with significant higher-multipole gravitational radiation [5].